A Google-based approach for monitoring suicide risk. (30th December 2016) - Solano, Paola; Ustulin, Morena; Pizzorno, Enrico; Vichi, Monica; Pompili, Maurizio; Serafini, Gianluca; Amore, Mario
Abstract: People seeking information and news regarding suicide are likely to use the Internet. However, evidence of the relationship between suicide-related search volumes and national suicide-rates in different countries can be strikingly different. We aimed to investigate the relationship between suicide-rates and Google suicide-related search volumes in the Italian population (2008–2012) using the Italian mortality database that provided monthly national data concerning suicides (2008–2012). Moreover, this study aimed to identify future trends of national suicide rates on the basis of the results we obtained concerning the period 2013-14. Google Trends provided data of online monthly search-volumes of the term "suicide", "commit suicide" and "how to commit suicide" in Google Search and Google News (2008–2014). Google Search volumes for the term "suicide" lags suicide by three months (ρ=0.482, p-value<0.001), whereas no correlation was found between search volumes for "commit suicide" and "how to commit suicide" and national suicide rates. Google News search volumes for the three terms resulted in white noise. Apparently, online searches for suicide-related terms in Italy are more likely to be linked to factors other than suicidiality such as personal interest and suicide bereavement. Highlights: Google Search volumes for "suicide" lag Italian suicides for 3 months (2008–2012). No association between suicide rates and Google searches for "how to commit suicide". No association between suicide rates and Google searches for "to commit suicide". Suicide-related Google News searches don't show statistically significant patterns.